2016
DOI: 10.1155/2016/9618795
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Relieves the Inflammatory Response and Enhances the Casein Expression in Bovine Mammary Epithelial Cells Induced by Lipopolysaccharide

Abstract: As one of functional active amino acids, L-arginine holds a key position in immunity. However, the mechanism that arginine modulates cow mammary inflammatory response in ruminant is unclear. Therefore, this study was conducted to investigate the effects of L-arginine on inflammatory response and casein expression after challenging the bovine mammary epithelial cells (BMECs) with lipopolysaccharide (LPS). The cells were divided into four groups, stimulated with or without LPS (10 μg/mL) and treated with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 57 publications
4
37
1
Order By: Relevance
“…3D). Our results are consistent with previous studies and showed that the expression of caseins were not significantly changed or even decreased when an animal is in mastitis [15,16] .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…3D). Our results are consistent with previous studies and showed that the expression of caseins were not significantly changed or even decreased when an animal is in mastitis [15,16] .…”
Section: Resultssupporting
confidence: 93%
“…However, the changes of different caseins are different. Using an ELISA method, it was found that β-casein decreased significantly during mastitis, while the content of α-casein did not change significantly [15] , which was in compliance with the results of several other studies [25,27] . In this study, we found that the content of α-casein of primary MECs did not change significantly under the stimulation of various concentrations of LPS, indicating that MA, WANG, GAO, NING LIU, LI, GAO, LU, CHEN the expression level of α-casein does not alter significantly during mastitis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, the protein expression of CSN2 and CSN3 also was reduced, which was consistent with their gene expression. This indicated that casein expression decreased when inflammation occurred in the bovine mammary epithelial cells after being stimulated by the pathogenic factors [52][53][54].…”
Section: Discussionmentioning
confidence: 93%
“…Recently, some studies revealed that Arg, a conditionally essential AA, also has some positive effects on the synthesis of milk protein (Mabjeesh et al, 2002;Doepel and Lapierre, 2011). Some recent studies (Chen et al, 2013;Wu et al, 2016) have demonstrated that the addition of Arg in culture medium increased casein protein synthesis in bovine mammary epithelial cells (BMEC). Moreover, Wang et al infused Arg through jugular vein in dairy cows to measure the effects of Arg infusion on milk protein synthesis in vivo.…”
Section: Introductionmentioning
confidence: 99%